2023
DOI: 10.1155/2023/4061592
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antiplasmodial, Cytotoxicity, and Antioxidant Activities of Lophira lanceolata (Ochnaceae): A Cameroonian Plant Commonly Used to Treat Malaria

Abstract: Background. Malaria is the leading cause of morbidity and mortality in African countries. We aimed this study at evaluating the in vitro antiplasmodial, antioxidant, and cytotoxicity activity of Lophira lanceolata extracts. Method. The aqueous and ethanol extracts were obtained by maceration. It tested in vitro the extracts against Plasmodium falciparum 3D7 and multiresistance Dd2. Macrophage cell lines (RAW 264.7 cells) and red blood cells were used for cytotoxicity tests. The antioxidant activity was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…These results show that the ethanol extract was active while the aqueous extract had moderate activity both for 3D7 sensitive and Dd2 resistant to strain. Similar results were observed by Abdel Azizi et al [ 11 ] when evaluating the In Vitro Antiplasmodial Cytotoxicity and Antioxidant Activities of Lophira lanceolata (Ochnaceae): A Cameroonian Plant Commonly Used to Treat Malaria. This could be explained by the nature of the solvent used for the extraction.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These results show that the ethanol extract was active while the aqueous extract had moderate activity both for 3D7 sensitive and Dd2 resistant to strain. Similar results were observed by Abdel Azizi et al [ 11 ] when evaluating the In Vitro Antiplasmodial Cytotoxicity and Antioxidant Activities of Lophira lanceolata (Ochnaceae): A Cameroonian Plant Commonly Used to Treat Malaria. This could be explained by the nature of the solvent used for the extraction.…”
Section: Discussionsupporting
confidence: 87%
“…Our results corroborate those obtained by Kodjio et al [ 12 ] where the ferric reducing power of the ethanol extract was greater than the aqueous extract on the evaluation of the antioxidant activity of the stem bark of K. grandifoliola . This high antioxidant power could be due to the strong presence of flavonoids and phenolic compounds [ 11 , 12 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cameroon, this disease is the main cause of consultation and the leading cause of morbidity and mortality [ 3 ]. Previous in vitro research work conducted by Abdel Azizi et al [ 4 ] and Guy-Armand et al [ 5 ] demonstrated that there is a close relationship between malaria and oxidative stress. According to these authors, during malaria infection, there is an overproduction of free radicals, which are toxic to the host organism.…”
Section: Introductionmentioning
confidence: 99%
“…Fermented palm wine (ethanol) or infusion is used by traditional practitioners for the preparation of medicinal remedies in Cameroon. Abdel Azizi et al [ 4 ] reported the in vitro antiplasmodial, cytotoxicity, and antioxidant activities of L. lanceolata. The study of Abdel Azizi et al [ 4 ] reported a moderate in vitro antiplasmodial activity of the aqueous extract according to the classification of Kumari et al [ 9 ] with IC 50 = 56.365 and 51.36 μ g/ml for sensitive and resistant strain, respectively, and resistance index of 0.09 (IR = 0.09).…”
Section: Introductionmentioning
confidence: 99%